The Potential of Eocene Shale of Nanggulan Formation as a Hydrocarbon Source Rock - Sarju Winardi, Sarju Winardi (CV Istana Kembar, 2013)
In western Indonesia, Eocene Shale is generally considered as a potential source rock. The Nanggulan Formation outcropping at Kulonprogo - Yogyakarta consist of a shale interval of Eocene in age. Analysis of its organic material content, kerogen type, and maturity level were conducted to know its potential. The laboratory analysis of eleven samples were done to measure its TOC content.